Acute Lyme neuroborreliosis with transient aphasia – Case report and review of current knowledge. (2022) - Cunha, Flávia; Duarte, Joana Alves; Gonçalves, Raquel
Abstract: Lyme borreliosis (LB) is a tick-borne infectious disease, endemic in the Northern hemisphere, with a polymorphic clinical spectrum (cutaneous, articular, and neurologic involvement). The variability of clinical manifestations poses LB as a diagnostic challenge. We describe a case of acute Lyme neuroborreliosis (LNB) in an adult female with a history of recent travel in Europe. There are few reports of acute LNB presenting as encephalitis in the literature. Suspicion for the diagnosis and prompt treatment seems to have a positive impact on patient outcomes.